Effectiveness of Mobile Health-Based Self-Care Education on Symptom Control and Quality of Life in Chronic Heart Failure Patients - Rogayah, Rogayah; Yanti, Lastri; Astuti, Yuniawati; Siswosuharjo, Partono (LPPM AKPER FATMAWATI, 2025)
Background: Chronic heart failure is a cardiovascular disease with a high morbidity burden that significantly impacts symptom control and patient quality of life. Self-care education is an important component in heart failure management, but conventional approaches are often suboptimal. The development of digital technology, particularly mobile health (mHealth), offers new potential in improving the effectiveness of education and patient engagement in self-care. Objective: This study aimed to analyze the effectiveness of mobile health-based self-care education on symptom control and quality of life in chronic heart failure patients. Methods: This study used a quasi-experimental design with a randomized controlled trial approach. A total of 80 chronic heart failure patients were randomly divided into an intervention group (n=40) and a control group (n=40). The intervention group received self-care education based on a mobile health application for 8 weeks, while the control group received conventional education. Symptom control was measured using the Heart Failure Symptom Score, and quality of life was assessed using the Kansas City Cardiomyopathy Questionnaire (KCCQ). Data analysis was performed using repeated measures ANOVA and mixed-effects models. Results: The study showed a significant reduction in symptom scores in the intervention group compared to the control group (p<0.001). Furthermore, there was a statistically significant improvement in quality of life in the intervention group (p<0.001). Compliance with application use was positively associated with improved clinical outcomes. Conclusion: Mobile health-based self-care education is effective in improving symptom control and quality of life in chronic heart failure patients and has the potential to be an innovative strategy in nursing practice